MENINGKATKAN KEMAMPUAN MENGENAL ANGKA MELALUI PERMAINAN TEBAK ANGKA BAGI ANAK TUNAGRAHITA RINGAN DI SDLB N MANGGIS GANTING BUKITTINGGI (Penelitian Tindakan Kelas di Kelas D I C) - Partini - Partini (Jurnal Penelitian Pendidikan Khusus, 2012)
This research begins with the inability of a problem that is not mentally impaired children of class D 1 C SDLB to master the learning of mathematics. Therefore, in this study researcher used a guessing game figures to enhance the ability of mentally impaired children in knowing numbers 1-10. This type of research is a class act who performed in collaboration with colleagues or classroom teacher. research subjects were Class D I C SDLB , three children Tunagrahita (Fd, Sv, Pt). The research was carried out using two cycles. The first cycle performed four times a second cycle of meetings and performed a total of four meetings. Data collected through observation, testing, and documentation. The results showed that the learning process increases the ability to know the numbers 1-10 through the game guess numbers can increase the ability of children which can result in the end in terms of states, shows and write numbers 1-10 have achieved 100% success. It can be concluded that through a number guessing game can improve children's ability to recognize numbers 1-10, it is advisable for teachers to apply the guessing game as one of the media figures that can be used to identify the numbers